Estudio de prefactibilidad para la instalación de una planta productora de jugo de Asaí (Euterpe oleracea) con plátano (Musa paradisiaca) en Lima Metropolitana - Chavez Cortez, Juan Carlos (2021)
In this research project, the market, technological, economic-financial and social feasibility of installing an asai beverage production plant was evaluated. The demand of the project reached 189,698 thousand liters of asai beverage in the last year of the project under the market segmentation criteria established according to the socioeconomic sector A, B and C between the ages of 18-55 years in Metropolitan Lima. The demand in juice bottles in the last year was 541,994 thousand units. Regarding the location of the production plant, the most relevant factors were determined to be proximity to suppliers and the target market. The macro location evaluation was carried out in the city of Lima, followed by a micro location evaluation, where it was determined that the plant should be located in the district of Huachipa. The size of production that the plant will have was determined by studying different factors, obtaining as a result that the size of the plant would be related to the size of the market. According to the engineering of the project to be used, it was determined that 10 machines and/or equipment will be necessary, the main one being the "slow pasteurization" machine, since it is responsible for giving the desired durability to the final product. There will be 16 operators for the entire production process, the production area will have an area of 120 m2 and the total area of the plant will be 800 m2. The economic and financial evaluation of the project was carried out, obtaining an economic NPV and IRR of 3,048,089 million and 28% respectively, and on the financial side, an NPV and IRR of 1,544,916 million and 15% respectively, demonstrating the economic and financial viability of the project.